System integration of geothermal heat plant in high-temperature district heating system - technical and economic issues - Tańczuk, Mariusz; Anweiler, Stanisław; Pochwała, Sławomir; Olszewski, Eligiusz; Łuczak, Paweł; Kalina, Jacek; Boldyryev, Stanislav (International Journal of Sustainable Energy Planning and Management, 2025)
Second-generation district heating (DH) systems based on coal combustion remain prevalent and inefficient in Central and Eastern Europe, particularly in Poland. This study investigates the technical and economic feasibility of integrating geothermal energy into an existing high-temperature DH system with a peak demand of 60 MW. Three retrofit scenarios are analyzed: (1) a geothermal doublet with a direct heat exchanger; (2) Scenario 1 extended by an absorption heat pump (AHP) powered by a gas boiler; and (3) Scenario 2 enhanced with an additional geothermal doublet. A detailed hour-by-hour simulation of thermal performance was conducted for each configuration. The share of geothermal heat in total production increases from 35% in Scenario 1 to nearly 70% in Scenario 3, enabling all variants to meet the efficiency thresholds defined in the EU Energy Efficiency Directive. An economic assessment using Net Present Value (NPV) and Internal Rate of Return (IRR) indicates that Scenario 1 is the most cost-effective, yielding an IRR above 17% and a 4-year discounted payback period. Although Scenario 3 achieves higher decarbonization, it requires significantly greater capital investment. The findings highlight that geothermal retrofitting, particularly with direct heat exchangers, offers a realistic and economically justified path for transforming legacy DH systems toward carbon neutrality.